2005
DOI: 10.1177/039463200501800419
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Evaluation of Tacalcitol Plus Puva versus Tacalcitol Plus UVB-NB in the Treatment of Psoriasis: “Right-Left Intra-Individual — Pre/Post Comparison Design”

Abstract: Photochemotherapy with psoralen plus ultraviolet A (pUVA) and phototherapy with UVB narrow band (UVB-NB) are used in the treatment of psoriasis. Numerous studies have shown that the additional administration of either topical or systemic antipsoriatic agents may effectively increase the efficacy of these therapies. This study aimed to compare through objective data the efficacy of topical tacalcitol in combination with PUVA or UVB-NB versus PUVA and UVB-NB monotherapy in the treatment of mild to moderate chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Several studies have been conducted to enhance the outcome of phototherapy through skin pretreatment with specific topical preparations (3–23). In this context, tar and petrolatum were reported to enhance the outcome of NB‐UVB; nevertheless, some authors reported some potential drawbacks due to the physical properties of the preparation that may lead to screening rather than enhancement of UVR (5, 19, 23–25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to enhance the outcome of phototherapy through skin pretreatment with specific topical preparations (3–23). In this context, tar and petrolatum were reported to enhance the outcome of NB‐UVB; nevertheless, some authors reported some potential drawbacks due to the physical properties of the preparation that may lead to screening rather than enhancement of UVR (5, 19, 23–25).…”
Section: Discussionmentioning
confidence: 99%
“…Trials were conducted on tar (3–5), anthralin (6), steroids (7), mineral oil, salicylic acid, petrolatum (5), calcipotriene (8, 9), and tazarotene (10). With the development of NB‐UVB, it represented a new target for combination trials with dithranol (11, 12), vitamin D derivatives (13–17), tazarotene (18), dithranol (14), petrolatum (19), oleic acid (20), mineral oil (21), saltwater (22), and tar (23). Although the outcome of these combinations was encouraging, the physical properties of the preparation, the thickness and/or the color of the film, represented a challenge to overcome the undesirable UV‐blocking effect (5, 24, 25).…”
mentioning
confidence: 99%
“…Eight grade A2 studies [116, 118, 121, 124, 163–165, 172], nine grade B studies [130, 133, 136, 166, 168, 173–176], and three grade C studies [177–179] were included on combination therapy with vitamin D and other topical or systemic therapies. A general distinction may be made between topical combination therapy, combination drugs (i.e., different active ingredients in one preparation), and sequential combinations of different preparations (i.e., agents in two different preparations).…”
Section: Topical Therapymentioning
confidence: 99%
“…Two studies on combination therapy with tacalcitol ointment have been included in the guidelines. Brazzelli et al [174] (EG B) reported a significant change in trans‐epidermal water loss (TEWL) and on corneometry, but not on visual scores. In other words, in terms of visible lesions, an eight‐week regimen of tacalcitol with UV therapy does not appear to be superior to UV monotherapy.…”
Section: Topical Therapymentioning
confidence: 99%
“…Yet a study on combination therapy with and calcitriol are roughly equally effective, it may be assumed that calcitriol therapy is more effective than tacalcitol 133,136,166,168,[173][174][175][176],. Use with salicylate-based keratolytics or dithranol preparations can diminish the effectiveness of the drug.…”
mentioning
confidence: 99%